x → ∞ lim x 2 ( 1 − c o s x 1 ) ( 1 − c o s x 1 ) ( 1 − c o s x 1 ) . . . = ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Without l'hopital the limit become more interesting :)
Log in to reply
I didn't use L'Hopital in my solution.
Log in to reply
I know. And I said it was an interesting solution. 👍
( 1 − c o s x 1 ) ( 1 − c o s x 1 ) ( 1 − c o s x 1 ) . . . = y 1 − y = c o s x 1 so x → ∞ lim x 2 ( 1 − c o s x 1 ) ( 1 − c o s x 1 ) ( 1 − c o s x 1 ) . . . = y → 0 lim ( c o s − 1 ( 1 − y ) 1 ) 2 × y cos − 1 ( 1 − y ) = x y → 0 lim ( c o s − 1 ( 1 − y ) 1 ) 2 × y = l i m z → 0 ( ( z 1 ) 2 × ( 1 − c o s ( z ) ) × 1 + c o s ( z ) 1 + c o s ( z ) ) = 2 1 If you like this solution upvote it and reshare the problem if you don't like it post another solution and reshare the problem also :)
How do you know the radical in the first line converge?
Log in to reply
Sorry but I didn't understand your question. Could you explain more.
Log in to reply
An infinitely nested function does not necessarily converge. See this
Log in to reply
@Pi Han Goh – The limit of the first line is exist when x approach to infinity and equal to zero
Log in to reply
@Refaat M. Sayed – how do you know that?
Log in to reply
@Pi Han Goh – Sir... Let y = 1 − c o s x 1 1 − c o s x 1 1 − c o s x 1 . . . . y = 1 − y c o s x 1 y 2 = 1 − y c o s x 1 y 2 + y c o s x 1 − 1 = 0 L e t , x 1 = t ⟹ t → 0 a s x → ∞
Can you take it from here?
Log in to reply
@Refaat M. Sayed – I know what you're trying to say. Like I said before, it is an infinitely nested function, the examples in the link I've sent you shows that not all nested functions converges.
Take this as another example: see this link . Are x = 2 and x = 4 both true at the same time?
Problem Loading...
Note Loading...
Set Loading...
Let α = ( 1 − cos ( x 1 ) ) ( 1 − cos ( x 1 ) ) ( 1 − cos ( x 1 ) ) …
So, we obtain 1 − cos ( x 1 ) α 2 = α
⇒ α = 1 − cos ( x 1 ) .
So we have the limit as:
x → ∞ lim x 2 α = x → ∞ lim x 2 ( 1 − cos ( x 1 ) ) = x → ∞ lim x 2 ⋅ ( 2 sin 2 ( 2 x 1 ) )
= x → ∞ lim 2 ⋅ ( 2 x 1 ) 2 sin 2 ( 2 x 1 ) = 2 1